Strengthening Wasathiyyah Islamic Values in the Perspective of Education in Madrasah - Tri Wibowo; Aziz Kurniawan (MUDARRISA: Jurnal Kajian Pendidikan Islam, 2023)
The research was motivated by concerns about religious conditions in Indonesia that are far from the word tolerance. Religious moderation is seen as a strategic value for building a true religious understanding amid religious issues that are sexy to discuss, often causing divisions and misunderstandings. The purpose of this study is to analyze and describe the process of strengtheing Wasathiyyah Islamic values developed through integrative thematic learning at MI Ma'arif NU 1 Pageraji Banyumas. The contribution of this article in the development of the science is to be a reference and patron of grounding the literacy movement at the primary education level. Research methods use qualitative research methods using a research approach thanks to the category of field research. The data collection methods used are observation, interviews and documentation. The data analysis technique used is the analysis technique of Miles and Huberman models. The results showed that the strengthening of Wasathiyyah Islamic values through integrative thematic learning was carried out with learning activities, religious activities, habituation and madrasah culture. The Wasathiyyah Islamic values developed include five core values, namely tawazun, tasamuh, i'tidal, shura and muwathonah values.